Pengaruh Masuknya Islam Terhadap Kebudayaan di Tanah Karo - Maulana, Ilham Aji; Manik, Deswita Saskia Humairah; Hutasiot, Siti Syarah; Siregar, Yusra Dewi (Medan Resource Center, 2024)
This study aims to examine the influence of the arrival of Islam on the culture in Tanah Karo, which was previously dominated by animism and dynamism beliefs. Through the literature review method, this research analyzes changes in the belief system, customs, marriage patterns, education, and social dynamics after Islam was introduced in the region. The findings show that interactions between Islamic traders and scholars with the indigenous Karo community triggered a slow but significant process of acculturation. Traditional Karo culture underwent a transformation, adopting Islamic values in various aspects of life, including religious celebrations like Eid al-Fitr, as well as in arts, architecture, and language. Despite challenges in the acculturation process, the Karo people managed to maintain a balance between local traditions and Islamic values, creating a pluralistic and dynamic cultural identity. This study is important for understanding cultural and religious dynamics in a diverse society and provides insights into the cultural evolution in Tanah Karo.